2013
DOI: 10.3109/01443615.2013.831048
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged laparoscopic surgery is associated with an increased risk of vertebral disc prolapse

Abstract: The benefits of laparoscopic surgery to the patient are well recognised, however it is more physically demanding on the surgeon. A survey was sent to members of the British Society of Gynaecological Endoscopy to ascertain musculoskeletal symptoms and vertebral disc prolapse thought to occur as a result of undertaking laparoscopic surgery. A total of 19 (15%) participants were diagnosed with a vertebral disc prolapse, for which one-third needed definitive treatment. There was a statistically significant associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 28 publications
1
27
0
2
Order By: Relevance
“…1 ). Twenty-one observational studies included only survey data [ 1 , 5 , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ], 10 studies evaluated muscle strain using EMG [ [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ], three studies incorporated both EMG analysis and survey data [ [37] , [38] , [39] ], and six studies used other tools such as pain scales and strain indices [ 1 , [40] , [41] , [42] , [43] , [44] , [45] ]. Of these only one study was a randomized case control design [ 28 ] while all other studies were non-randomized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Twenty-one observational studies included only survey data [ 1 , 5 , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ], 10 studies evaluated muscle strain using EMG [ [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ], three studies incorporated both EMG analysis and survey data [ [37] , [38] , [39] ], and six studies used other tools such as pain scales and strain indices [ 1 , [40] , [41] , [42] , [43] , [44] , [45] ]. Of these only one study was a randomized case control design [ 28 ] while all other studies were non-randomized.…”
Section: Resultsmentioning
confidence: 99%
“…Many surgeons have experienced a work-related injury such as cervical spinal stenosis, lumbar disc herniation, or carpal tunnel syndrome [ [1] , [2] , [3] , [4] , [5] ]. These injuries result in surgeons undergoing surgery themselves, taking leaves of absence, and even retiring earlier than planned [ 1 , 5 ]. Chronic pain, numbness, and fatigue also may occur from years of manual labor rather than as a result of a specific injury, while still potentially limiting overall work performance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have described a high level of ergonomic and mental stress among surgeons performing minimally invasive surgery compared to open procedures. [45][46][47][48] The surgeons in the present study reported open surgery as the most common procedure, but this is likely to change due to the rapid increase in minimally invasive surgery. Those surgeons who performed both techniques reported the laparoscopic approach to be the most painful procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons encounter musculoskeletal strain and disorders resulting from long periods of muscle tension and awkward poses 1 3 . Injuries to surgeons include pain in specific areas of the body, vertebral disk prolapse and carpal tunnel syndrome 4 , 5 . These issues are closely related to the mental and physical workloads of surgeons during surgery 2 .…”
Section: Introductionmentioning
confidence: 99%